Implementation of Ergonomics and Local Wisdom in Designing ErJo (Ergonomic Jojodog) as a Solution to the Sustainability of Squatting Work - Rahdiana, Nana; Hakim, Afif; Amalia, Amalia; Sahat Marihot, Louwis Perdian; Tri Aditya Anuraga, Tito; Hajin, Nasirul; Hutami Rahmadianti, Putri; Herawati, Herni; Raeni, Ida; Majid, Falahal; Yanfahira Shafa, Kezia; Wiguna, Rahmat (SPEKTA (Jurnal Pengabdian Kepada Masyarakat : Teknologi dan Aplikasi), 2025)
Background: This community service program was implemented to address musculoskeletal complaints among production workers who frequently adopted squatting postures, which imposed static loads on the lower back, knees, and calves, resulting in discomfort and reduced productivity. Contribution: This study introduces ErJo (Ergonomic Jojodog), a culturally adaptive ergonomic innovation that integrates traditional sitting design with modern ergonomic principles to enhance worker comfort and foster cultural acceptance. Method: A participatory ergonomics approach involving ten production workers was employed through design, testing, and evaluation stages. Musculoskeletal complaints were assessed using the Indonesian National Standard (SNI 9011:2021), complemented by field observations and semi-structured interviews. Results: After two weeks of ErJo implementation, musculoskeletal complaints in the knees and calves decreased from 67% to 20%, while lower-back discomfort declined to 40%. Participants reported greater comfort, stability, and ease of movement, with the belt-equipped model achieving the highest usability score. This study demonstrates that integrating ergonomics with local wisdom enhances worker well-being and promotes sustainable occupational practices. Conclusion: ErJo effectively reduced musculoskeletal complaints and improved work comfort in squatting tasks. This innovation supports SDG 3 (good health and well-being) and SDG 8 (decent work and economic growth), with potential for broader application across similar manual occupations.